Desenvolvimento de um material paradidático para o ensino de física utilizando a astronomia como tema motivador - Rosado, Ricardo Meloni Martins (Universidade Federal de São Carlos, 2012)
This work relates the development and application of a teaching aid Physics material using Astronomy as a motivating theme. To achieve such goal, an extension course was set to teach physical concepts, especially those in the field of Mechanics, from Astronomy to high school and graduation students. The material covers such concepts as Referential, Gravitational Field, Kepler Laws, Newton Laws, Evolution of Universe Conception Models, Mass Centre and others. At the end, some results about the application of this material are shown, as well as the possibilities and difficulties found by its application. The whole material and its questionnaires and activities made by students are presented in the annex.
Keywords: Física - estudo e ensino; Física - ensino; Astronomia - ensino -; Motivação na educação; Materiais didáticos; Physics teaching; Astronomy teaching; Didactic materials; CIENCIAS EXATAS E DA TERRA::ASTRONOMIA